Between Criticality and Conformism: Citizenship and Education in Post-independent India. (January 2022) - Kumar, Avinash
This article attempts to investigate the three strands of citizenship, nationalism and education and their interconnectedness in India after independence. It seeks to address questions like how has the post-colonial state in India visualized its models of citizenship through its education policies and programmes and what has become of their fate? In what ways the changing nature of public versus private education has shaped contested models of citizenship? What challenges are thrown at the models of citizenship that the Indian state has tried to posit through education? It is argued that the journey of citizenship in post-independent India is that of contradictory pulls around key strands of ethno-cultural nationalism and civic nationalism and around an economically productive nation versus an economic consumer nation. The article will look at some of the key policy shifts and operational models and attempt to locate the dynamic behind those shifts.